Pengaruh Online Customer Review, Influencer dan Affiliate Marketing pada Media Sosial Tiktok terhadap Minat Beli Produk Fashion Mahasiswa - Nurvianti, Rida; Hartiningtyas, Lavita (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to examine the influence of Online Customer Reviews, Influencers and Affiliate Marketing on Purchase Intentions. In addition, it also aims to determine how much influence Online Customer Reviews, Influencers and Affiliate Marketing simultaneously have on Buying Interest. This research approach is quantitative with the type of associative research. The sample of this research is UIN Sayyid Ali Rahmatullah Tulungagung Islamic Economics and Business Faculty students who have made purchases on Tiktok. The analysis technique used is multiple linear regression with a sample of 75 respondents using a closed questionnaire method. The results of data analysis and hypothesis testing show that Online Customer Reviews and Influencers have no significant effect on purchase intention. Meanwhile Affiliate Marketing has a significant effect on purchase intention Keywords: Customer Online Review, Influencer, Affiliate Marketing, Buying Interest, Fashion, Tiktok